Validity and reliability of the questionnaire of Chinese self-efficacy for Chinese as a second language learners in China - Peng, Yulan; Zainal, Muhammad Zuhair (Institute of Advanced Engineering and Science, 2025)
Self-efficacy is a pivotal predictor of academic success in second language learning. With the growing enrollment of international students in Chinese language programs in China, there is a pressing need for validated tools to assess self-efficacy among Chinese as a second language (CSL) learners. This study addresses this need by adapting and validating the English-Chinese questionnaire of Chinese self-efficacy (QCSE) from the original questionnaire of English self-efficacy (QESE). Using a cross-sectional design, data were collected from 174 international college students in Jiangxi Province for psychometric evaluation. Confirmatory factor analysis (CFA) assessed the instrument’s reliability and validity, with results showing a high overall Cronbach’s alpha of 0.942 and strong dimension-specific values (listening, speaking, reading, and writing) ranging from 0.915 to 0.927. All item outer loadings exceeded 0.7, and the average variance extracted (AVE) values were above 0.5, confirming the robustness of the QCSE. This validated instrument addresses a critical gap in CSL self-efficacy assessment and provides valuable insights for learners, educators, and policymakers.